Flaubert lecteur : une histoire des écritures - Philippe Dufour (Flaubert: Revue Critique et Génétique)
Flaubert reads to write. During the 1845-1857 period in particular his literary readings perfect his training and provide him with his esthetics, in a game of confrontations. We find on the one hand the admired figures of the past, whether they be the great naïve geniuses who inspire Flaubert’s dogma of impersonality, or the masters of the classical age, who remind the inspired writer to be patient. Then, on the other hand, there are the rejected contemporary figures: formless works of sentimental Romanticism, or the Realist’s artless works, industrial literature’s soulless works. By placing himself in the field of the literary possibilities Flaubert writes a history of writings.